發新話題
打印

用複數表示「平行四邊形定理」

推到噗浪
推到臉書
對於任意平行四邊形 \(ABCD\),

不失一般性,可以將其平移到以 \(A\) 為原點 \(0+0i\),

設 \(B=a+bi\), \(D=c+di\),其中 \(a, b, c, d\) 為實數,

因為 \(ABCD\) 為平行四邊形,則 \(C=(a+c)+(b+d)i\),

求證 \(2(AB^2 + AD^2) = AC^2 + BD^2\).



證明:

左式\(= 2(AB^2 + AD^2)\)

  \(= 2\left(|(a+bi)-(0+0i)|^2 + |(c+di)-(0+0i)|^2\right)\)

  \(= 2\left((a^2+b^2) + (c^2+d^2)\right)\)


右式\(= AC^2 + BD^2 \)

  \(= |((a+c)+(b+d)i) - (0+0i)|^2 + |(a+bi)-(c+di)|^2\)

  \(= \left((a+c)^2+(b+d)^2\left) + \right((a-c)^2+(b-d)^2\right) \)

  \(=2a^2+2b^2 + 2c^2+2d^2\)

故,左式=右式,得證。

TOP

發新話題